Avaliação dos efeitos do canabidiol sobre os eventos imunológicos e degenerativos induzidos pela encefalomielite autoimune experimental (EAE) em camundongos - Thiago Vitarelli da Silva (2013)
Multiple sclerosis is a progressive and disabling disease neurologically more common among young adults. The disorder is characterized by the occurrence of demyelination, chronic inflammation, axonal and oligodendrocytes loss. Understanding the immuno-pathological mechanismsand possible treatments is a major challenge. Toelucidate some of these issues, the use of animal models, that reproduce the disease changes, represent a useful tool. Among the models available, highlights the experimental autoimmune encephalomyelitis (EAE) induced by immunization with neuropeptides. The cannabidiol (CBD) is the main component of Cannabis sativadevoid of psychoactive effects. Its neuroprotective, anti-inflammatory and antioxidants properties have been documented in studies of various disorders. From this scenario, the goal of this investigation was to evaluate the effects of chronic and prophylactic treatment with CBD on immune and degenerative events of EAE. To reach this aim, C57BL/ 6 female mice (10-12 weeks, 17-20 g) were divided into four groups.Two groups were subjected to EAE model induction, one being treated daily with CBD (5 mg/kg, i.p.) from day 0 to 14 post induction and the second was treated with vehicle (5% Tween). Control groups were divided similarly into vehicle and CBD. The EAE was induced by subcutaneous injection of an emulsion containing 100g MOG 35-55 plus 4mg/ml of Mycobacterium tuberculosis H37Ra in Freud's Complete Adjuvant. Pertussis toxin (300 ng/animal, i-p.) was injected on the day ofimmunization and 48 h later. The animals were monitored daily for body weight and clinical manifestations, across a range of scores, and periodically for motor (Rotarod) and sensory (Tail Flick) tests. The therapy used was not effective in reversing the progression and severity of the clinical model. On day 14 post induction, there was visualization of leukocyte adhesion and rolling by intravital microscopy technique, and integrity of the blood brain barrier by measuring of Evans blue dye extravasation in the brain and spinal cord. The expression of adhesion molecules (VCAM-1, ICMA-1) was also evaluated, only in the spinal cord, by RT-PCR and the inflammatory cell infiltration. In relation to theseparameters, the drug attenuates central inflammation observed in the model. The indirect determination in serum nitric oxide (NO) by Griess reaction, indicated that treatment increased the bioavailability of this mediator in EAE, which possibly may have contributed to some of the effects mentioned. The in vitro evaluation, by the MTT reduction assay, confirmed the ability of CBD to inhibit proliferation of splenic cells in response to MOG35-55 by a mechanism independent of G protein. However, the immunosuppressive activity of the drug was notobserved in vivo, since the treatment did not reverse the increased total count of the leukocytes in the peripheral circulation seen in EAE animals. The therapy, though, was not able to reverse the decline of characteristicdegenerative events ofthe model, demyelination and axonal damage, evaluated respectively by staining for LFB and neurofilament-Hexpression. In summary, this study suggests that CBD attenuated the inflammatory process in EAE by interfering in various events related to leukocyte migration into the CNS. Nevertheless, the cannabinoid did not alter the degenerative process which reflects, inpart, its clinical inefficacy on the animal model.